Execution - Parris, S. J., 1974- (Parris, S. J., 1974- Giordano Bruno thriller., 2020)
"Giordano Bruno, a heretic turned spy, arrives in England with shocking information for spymaster Sir Francis Walsingham. A band of Catholic Englishmen are plotting to kill Queen Elizabeth and spring Mary Queen of Scots from prison to take the English throne in her place. Bruno is surprised to find that Walsingham is aware of the plot--led by the young, wealthy noble Anthony Babington--and is allowing it to progress. He hopes that Mary will put her support in writing--and condemn herself to a traitor's death"--Publisher marketing.